2020
DOI: 10.1097/scs.0000000000006545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficiacy of Intra-Articular Injection of Liquid Platelet-Rich Fibrin and Hyaluronic Acid After in Conjunction With Arthrocentesis for the Treatment of Internal Temporomandibular Joint Derangements

Abstract: The aim of this study was to evaluate the effectiveness of intra-articular injection of liquid platelet-rich fibrin (I-PRF) versus hyaluronic acid (HA) following arthrocentesis in patients suffering from temporomandibular joint (TMJ) pain and dysfunction. A total of 69 patients with internal TMJ derangement were enrolled in this retrospective, matched cohort study. A total of 47 included patients (67 joints) were divided into 3 groups as follows: 16 participants in the arthrocentesis-only group; 14 patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
2
29
1
1
Order By: Relevance
“…In addition, there was statistically significant difference regarding all these studied parameters within the i-PRF group between baseline and 6 months follow up. Our results agreed with Yuce et al., 33 who compared the efficacy of arthrocentesis alone, arthrocentesis followed by HA injection, and arthrocentesis followed by i-PRF injection and revealed significant decrease in pain and increase in maximum inter-incisal opening in the study group. Similarly, Hancı et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, there was statistically significant difference regarding all these studied parameters within the i-PRF group between baseline and 6 months follow up. Our results agreed with Yuce et al., 33 who compared the efficacy of arthrocentesis alone, arthrocentesis followed by HA injection, and arthrocentesis followed by i-PRF injection and revealed significant decrease in pain and increase in maximum inter-incisal opening in the study group. Similarly, Hancı et al.…”
Section: Discussionsupporting
confidence: 92%
“…Torul et al., 30 showed that injection of i-PRF appeared to have significant long-term promising effects in the management of TMJ internal derangement which can be related to its ability to selectively enrich leukocytes, platelets, growth factors and cytokines within its liquid matrices. 1 , 18 , 19 , 33 Our results disagreed with Albilia et al. 1 where no statistically significant decrease in pain score was obtained in the i-PRF group and the increase in maximum mouth opening was insignificant for all patients.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…[20][21][22] Wilkes stages. 12 Yuce et al 23 in their study comparing arthrocentesis alone with addition of either HA or i-PRF showed significant benefits with addition of i-PRF compared with arthrocentesis alone in terms of VAS scores and MMO. Hydraulic adheolysis, elimination of negative pressure in the superior joint space, restoration of the synovial viscosity and growth factor release and circulation are the reason behind the effect of PRF.…”
Section: Discussionmentioning
confidence: 97%
“…In knee arthrosis, degenerative disc disease (intradiscal treatment), facet pathologies (intrafacial injection), and sacroiliitis, reduced pain scores and increased functionality were observed after platelet-rich plasma therapy [ 75 ]. Improvement can also be observed in severe temporomandibular joint disorders through platelet-rich fibrin injection after arthrocentesis into the upper join space or with adjuvant platelet-rich plasma insertion during arthroscopy procedures or arthrocentesis [ 76 , 77 ].…”
Section: Therapeutic Use Of Platelet Rich Concentrates In Human Diseasesmentioning
confidence: 99%